Przestrzenne zróżnicowanie usług gastronomicznych w Polsce - Sala, Józef (Wydział Prawa i Administracji UAM, 1986)
The post-war period brought about a rapid development of both open and closed catering in many countries. Presently, in the developed countries it became an important link in the complex of provision business and tourism. In Poland, in the last 40 years that development was poor. That is why synchronizing spatial structures of supply and demand for catering services becomes an important task. On the basis an analysis produced in the article, with the use of taxonomic methods, it has (to be stated that the largest disparities in the spatial structures of demand and supply for catering services are observed in the city agglomerations and in the area of Central-Eastern Poland. It results in determined effects for the population. First of all it can influence differentiation of living standard and negatively affects the level of nourishment of the society. Therefore, the ascertained deviations in development must be eliminated in the course of the implemented economic reform.
Spatial distribution of catering services in Poland